1850 Mass. Acts 401, ch. 194, sec. 2 - (:unkn) unknown (General Publisher, 1850)
Prohibited the manufacture or sale of slung-shots. Violators fined not less than fifty dollars or imprisoned not exceeding six months.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS